Development of the database for information system of definition of the centers of toxicity of water ecosystems - Порван, Андрей Павлович; Высоцкая, Елена Владимировна; Беспалов, Юрий Гаврилович; Носов, Константин Валентинович; Пащенко, Мария Алексеевна (Technology audit and production reserves, 2013)
The paper considers the use of modern methods and tools for timely detection of the centers of toxicity formation in water bodies that is often associated with finding and processing of a set of various parameters, which are performed manually or using small programs that leads to the excess expenditure of time and information overload of specialists. The problem of the data processing automation or, at least, the manual handling complexity reduction, is also present during the biological monitoring in the zone of influence of potentially dangerous objects. For the solution of this problem, there is a need of creation of the corresponding specialized database for the information system of the definition of toxicity centers in water bodies, which provides complete independence of the data, the manipulation of which at the level of the control system language does not require the development of additional software and is not attached to the structure of the database.